KONTESTASI DAN GENEALOGI â€œKEBANGKITANâ€ ISLAM NUSANTARA: KAJIAN HISTORIOGRAFIS BABAD TANAH JAWI - Bakir, Bakir; Fawaid, Achmad (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
From the first writing of 1612 to the 'final version' in 1836, the Babad Tanah Jawi (BTJ) has always been debated mainly regarding its function as genre, prophecy, historical narrative, genealogical prototypes, and testimonial structures on Javanese history. Nevertheless, it is rare for the study of how Islam Nusantara, specifically described in the Babad Tanah Jawi, is considered to have a 'problematic' double genealogy as the effect of the breaking down of the basket between Batara Guru and Prophet Adam, a discrepancy that reflects Islam Nusantara as the result of a syncretistic forces between (Islam) Demak and (Hindu) Majapahit. This study seeks to illustrate the scholarly contestation of the double gynowogy of the Islamic revival of the archipelago after the fall of Majapahit and its implications for the ambivalent narratives of insurrection in Babad Tanah Jawi, a text that sparked much debate among anthropologists, philologists and archaeologists of the world, Pararaton and Nagarakertagama - many referred by anyone who wants to learn about Islam and Javanese kings.